Description of a peatland complex in an agricultural landscape on Terceira Island (Azores): Criação do Filipe Case Study - Cândida Mendes (International Mire Conservation Group and International Peat Society, 2021)
The Criação do Filipe peatland complex on Terceira Island (Azores) includes a fragmented network of inter-connected peatlands that have persisted over time within an agriculture-dominated landscape. This study identifies a number of human pressures including cattle grazing in and around the mire, a high population density of rabbits, high cover of exotic plant species and the presence of infrastructure (stone walls, electricity poles, etc.). The peatland complex has 44 plant species including four Sphagnum species, ten endemic vascular plants and eight plant communities. The maximum peat depth is seven metres. The peatlands receive inputs of water from streams entering at their northern margins, particularly from two pumice-extravasated cones, in addition to precipitation and intercepted fog. Accumulated water feeds other wetlands downstream. The complex shows increasing cover of aggressive and natural woody species, and water table levels are lower now than they were in 1998. Given its importance as one of the largest peatland complexes within Terceira Island’s anthropic landscapes, which is partially protected by the European Habitats Directive and located within a Natura 2000 network area as well as in Terceira Natural Park, the Criação do Filipe area should be the target of an active restoration/conservation plan.